2022
DOI: 10.3390/brainsci12020185
|View full text |Cite
|
Sign up to set email alerts
|

No Change in Inhibitory Control or P3 Following Different High-Intensity Interval Exercise Modalities

Abstract: Acute aerobic high-intensity interval exercise (HIIE) has demonstrated positive effects on inhibitory control and P3 event-related potential (ERP) in young adults. However, the evidence is not well established regarding the effects of different HIIE modalities that incorporate aerobic-resistance training on these cognitive and neurocognitive outcomes. The purpose of this investigation was to examine the transient effects of HIIE-aerobic and HIIE-aerobic/resistance on P3 and Flanker task performance. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…These mixed results could be related to the intensity of the acute aerobic exercise. Similar to the current findings, Su et al [ 36 ] found no change in inhibitory control or the magnitude of electroencephalographic P3 event-related potentials after acute high-intensity exercise intervention [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…These mixed results could be related to the intensity of the acute aerobic exercise. Similar to the current findings, Su et al [ 36 ] found no change in inhibitory control or the magnitude of electroencephalographic P3 event-related potentials after acute high-intensity exercise intervention [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although there is growing body of literature supporting the effects of HIIE on cognition ( Ai et al., 2021 ; Alves et al., 2014 ; Tsukamoto et al., 2016 ), the underlying mechanisms of HIIE on cognitive function remains unclear ( Drollette et al., 2022 ; Kao et al., 2018 ; Kao et al., 2017 ; Tsai et al., 2021 ). Event-related potentials (ERPs), derived from the ongoing electroencephalogram (EEG), are a relatively non-invasive high temporal resolution methodology that can be used to reveal precise neurocognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…ERPs have been used to examine neurocognitive mechanisms underlying the effects of acute exercise on general cognitive function ( Chu et al., 2015 ; Fearnbach et al., 2016 ; Fearnbach et al., 2017 ; Hanlon et al., 2012 ; Kao et al., 2022 ; Levin et al., 2021 ; Ludyga et al., 2017 ; Themanson & Hillman, 2006 ) and food-related cognition among individuals with overweight and obesity ( Chu et al., 2015 ; Fearnbach et al., 2016 ; Fearnbach et al., 2017 ; Hanlon et al., 2012 ; Kao et al., 2022 ; Levin et al., 2021 ; Ludyga et al., 2017 ; Themanson & Hillman, 2006 ). The P3 component is one of the mostly frequently examined ERP components in this area ( Drollette et al., 2022 ; Kao et al., 2018 ; Kao et al., 2017 ; C. L. Tsai et al., 2021 ), although the late positive potential (LPP), a response to stimulus significance that has been defined in terms of the activation of appetitive and aversive motivational systems, has been studied less frequently using food-related cognitive tasks ( Carbine et al., 2018 ; Hanlon et al., 2012 ). Our previous study examined this ERP component in obese populations ( Xie et al., 2020 ), and we found that LPP amplitude, but not the P3, was facilitated after a 30-min session of HIIE, suggesting an increased attentional allocation and cognitive control after a single bout of HIIE.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a systematic review found increased inhibitory control after weeks of computer‐based training, also known as cognitive training 23 . Intriguingly, some studies observed that inhibitory control performance is improved during moderate‐intensity exercises, which seems to occur in an inverted U shape with decreased performance in low‐ and high‐intensity exercises 24,25 . Also, inhibitory control performance during rest and exercise is not correlated, 26 indicating that inhibitory control training combined with exercise might generate different results than those training separately.…”
Section: Introductionmentioning
confidence: 99%
“…23 Intriguingly, some studies observed that inhibitory control performance is improved during moderate-intensity exercises, which seems to occur in an inverted U shape with decreased performance in low-and high-intensity exercises. 24,25 Also, inhibitory control performance during rest and exercise is not correlated, 26 indicating that inhibitory control training combined with exercise might generate different results than those training separately. Despite the evidence of improving inhibitory control after a short period of cognitive training, 23 it is important to highlight that this effect may not occur for athletes.…”
Section: Introductionmentioning
confidence: 99%